Edukasi Keuangan Remaja di SMA Negeri 5 Kupang sebagai Upaya Mencegah Risiko Perilaku Finansial - Maria Goreti Malut; Susana Purnamasari Baso; Leopold Melkiano Triangga Dawu; Kristina Wada Betu; Elda Riwu; Desidaria Ayuhandini Jagu (Universitas Negeri Gorontalo, 2025)
Teenagers are vulnerable to risky financial behaviors such as online gambling and digital loans due to low financial literacy and high digital access. To address this issue, a community service program was carried out at SMA Negeri 5 Kupang aiming to improve students’ understanding and basic skills in personal financial management. The methods included interactive lectures, financial recording simulations, group discussions, and evaluation through pre-tests and post-tests. A total of 50 students from grades X and XI participated, guided by accounting students and teachers. Results showed that 86% understood basic financial concepts, 76% were able to create simple budgets, 64% became familiar with youth-friendly financial products, and 42% were motivated to set long-term financial goals. Participants also showed strong enthusiasm and began tracking daily expenses. The school’s support further strengthens the sustainability of the program. These findings confirm that a contextual and practical educational approach effectively fosters wiser and more responsible financial behavior among adolescents.